Penerapan Strategi Pembelajaran Langsung Interaktif dalam Pengajaran Materi Berbentuk Konsep pada Mata Pelajaran Pendidikan Agama Islam - Dhobith, Anwar; Ratnasari, Dwi; Latipah, Eva (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The purpose of the research is to provide an overview to educators regarding the practice of implementing direct interactive learning strategies, in which errors considered common often occur. In this case, they are not believed to be mistakes, whereas they are not implemented by the theory, such as the absence of implementation of clarification in the learning process. Methods – This research is qualitative type. Therefore, the data is collected by observation. Observations were carried out in the classrooms of students of the 5th semester Islamic Religious Education study program at Sunan Kalijaga State Islamic University, Yogyakarta. The data analysis used is the Miles and Huberman model, consisting of steps for data reduction, data presentation, and conclusion. Findings – The results of this research indicate that the implementation of interactive learning strategies in the classroom contains a sequence of steps by theory, commencing with goals and establishing a set, explanation or demonstration of knowledge, guided practice, checking understanding and providing feedback, as well as extended practice and expanding transfers. Nonetheless, the two steps are combined into one by the educator who implements them.Research Implications – This research is limited to the application of interactive direct learning strategies. In this case, the obstacle in this strategy is the difficulty in generalizing several steps in the learning strategy since there are steps combined into one. The researcher hopes that this research can be a guide for educators in implementing interactive direct learning strategies in the classroom.